Māori, pharmacists, and medicines adherence - A mixed methods study exploring indigenous experiences of taking medicines 'as prescribed' and mechanisms of support - Joanna Hikaka; Nora Parore; Robert Haua; Anneka Anderson; Mariana Hudson; Brendon McIntosh; Kevin Pewhairangi; Rachel Brown (Elsevier, 2022)
Background: Medicines are the most common medical intervention and medicines adherence is associated with improved clinical outcomes. Understanding drivers and experiences of medicines adherence is important for optimising medicines use. Māori (Indigenous people of Aotearoa New Zealand) experience inequities in access to medicines yet little evidence exists regarding Māori and medicines adherence, or the role of pharmacists in supporting medicines adherence for Māori. Objectives: To explore Māori experiences of medicines adherence and non-adherence, and pharmacists' role in supporting adherence. Methods: This was a convergent parallel mixed methods study. Facilitated wānanga (collaborative knowledge-sharing group discussions) were undertaken either online or in-person with eligible participants, using convenience and snowball sampling to recruit. Participants were eligible if they were Māori, 18 years or older, and had recently obtained medicine from a pharmacy. Wānanga involved semi-structured interviewing and questionnaire completion. General inductive coding and thematic analysis and descriptive statistical analysis were used respectively, and findings were situated in social, cultural and political Māori contexts. Results: Thirteen wānanga were conducted with 62 participants (71% female, median age range 35-44) from September 2021 to February 2022. Four themes were identified: The aspirations of hauora Māori (Māori wellbeing) - medicines as a component of holistic wellbeing; whanaungatanga (relationships); knowledge; and whānau (family and support network) advocacy and problem solving. Forgetting to take medicines was the most frequently identified reason for non-adherence, followed by not having medicines on hand, adverse effects, and lack of symptoms of health conditions. Participants identified that proactive pharmacist support, including developing caring therapeutic relationships, sharing knowledge, acknowledging medicines as just one component of holistic wellbeing, and giving adherence tips to support routine medicine taking were positive ways that pharmacists could support medicines adherence. Conclusions: Factors contributing to medicines adherence were diverse and participants identified numerous practical solutions that pharmacists, health service providers and policymakers could employ to support Māori medicines adherence.